Hybrid Modification of Stone Mastic Asphalt with Cellulose and Basalt Fiber - You Huang; Zhaohui Liu; Li Liu; Yunbao Zhang; Qingxiang Xu (Advances in Materials Science and Engineering)
In this study, cellulose and basalt fiber were introduced simultaneously to stone mastic asphalt (SMA) to investigate the effects of hybrid modification on performance improvement of asphalt mixture. The study consists of three parts. The first part investigated material properties of cellulose and basalt fiber, including microscope electrical scanning. The second part conducted a series of tests to evaluate the effects of different combinations of cellulose and basalt fiber on performance. With a total addition of fiber 0.4% by the weight of mixture, five different cellulose-basalt fiber ratios, 0 : 4, 1 : 3, 2 : 2, 3 : 1, and 4 : 0, were introduced to the asphalt mixtures. A series of tests including draindown, permanent deformation, low temperature bending, beam fatigue, and moisture damage resistance were conducted. In the final part, a benefit-cost ratio was designed to help determine the optimum cellulose-basalt fiber combination in the economic aspect. Results show that material properties of the two fibers are very different, including thermostability, modulus, surface, and microstructure, especially oil absorption. In general, all samples with fibers outperformed the control group in all the performance tests. Specifically, cellulose fiber improved draindown, ductility, and fatigue more significantly, whilst basalt fiber has more influence on improving permanent deformation, deflection strength, and stress sensitivity. Equal portion of cellulose and basalt fiber has the best moisture damage resistance. The mechanisms of the two fibers are different, resulting in different performance improvements on asphalt mixtures. Overall, an appropriate combination of the two fibers would produce paving materials with more balanced performance in an economical way.